Modern Prodrug Design for Targeted Oral Drug Delivery - Arik Dahan; Ellen M. Zimmermann; Shimon Ben-Shabat (Molecules, 2014)
The molecular information that became available over the past two decades significantly influenced the field of drug design and delivery at large, and the prodrug approach in particular. While the traditional prodrug approach was aimed at altering various physiochemical parameters, e.g., lipophilicity and charge state, the modern approach to prodrug design considers molecular/cellular factors, e.g., membrane influx/efflux transporters and cellular protein expression and distribution. This novel targeted-prodrug approach is aimed to exploit carrier-mediated transport for enhanced intestinal permeability, as well as specific enzymes to promote activation of the prodrug and liberation of the free parent drug. The purpose of this article is to provide a concise overview of this modern prodrug approach, with useful successful examples for its utilization. In the past the prodrug approach used to be viewed as a last option strategy, after all other possible solutions were exhausted; nowadays this is no longer the case, and in fact, the prodrug approach should be considered already in the very earliest development stages. Indeed, the prodrug approach becomes more and more popular and successful. A mechanistic prodrug design that aims to allow intestinal permeability by specific transporters, as well as activation by specific enzymes, may greatly improve the prodrug efficiency, and allow for novel oral treatment options.